Dobutamine, Epinephrine, and Milrinone Accelerate Particle Transport Velocity in Murine Tracheal Epithelium via Ca2+ Release from Caffeine-Sensitive Internal Stores - Götz Schmidt; Frederic Borchers; Sabrina Müller; Amir Ali Akbari; Fabian Edinger; Michael Sander; Christian Koch; Michael Henrich (Cells)
Mucociliary clearance, the ability of the respiratory tract to protect the integrity of the airways through the mechanical removal of potentially harmful substances, is of enormous importance during intensive care treatment. The present study aimed to evaluate the influence of clinically relevant inotropic agents on mucociliary clearance. The particle transport velocity (PTV) of isolated murine tracheae was measured as a surrogate for mucociliary clearance in the presence of dobutamine, epinephrine, and milrinone. Inhibitory substances were applied to elucidate the signal transduction cascades and the value and origin of calcium ions which provoke alterations in mucociliary clearance function. Dobutamine, epinephrine, and milrinone increased the PTV in a dose-dependent manner with half maximal effective concentrations of 75.7 nM, 87.0 nM, and 13.7 µM, respectively. After the depletion of intracellular calcium stores, no increase in PTV was observed after administering any of the three inotropic agents. While dobutamine and epinephrine activated β-adrenergic receptors, epinephrine used both the phospholipase C (PLC) and protein kinase A (PKA) pathway to promote the release of intracellular Ca2+. However, dobutamine primarily acted on the PKA pathway, having only a minor influence on the PLC pathway. The induced changes in PTV following milrinone administration required both the PKA and PLC pathway, although the PKA pathway was responsible for most of the induced changes. In conclusion, the common inotropic agents dobutamine, epinephrine, and milrinone increase murine PTV in a concentration-dependent manner and ultimately release Ca2+ from intracellular calcium stores, suggesting the function of changes in mucociliary clearance in the respiratory tract.